PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA MATA PELAJARAN IPA UNTUK KELAS V SEKOLAH DASAR - Nike Minarti; Meria Ultra Gusteti (Jurnal Riset Pendidikan Dasar Dan Karakter, 2025)
This study aims to develop a Pop-Up Book learning media on the water cycle topic for fifth-grade elementary school students and to examine its validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method using the 4-D development model, which includes the stages of define, design, develop, and disseminate. The research subjects consisted of expert validators, classroom teachers, and fifth-grade students. The instruments used were validation sheets, practicality questionnaires, and student learning outcome tests. Data were analyzed using descriptive percentage analysis and gain score analysis to measure the improvement in learning outcomes. The results showed that the Pop-Up Book media achieved a very high level of validity based on evaluations by material and media experts. Its practicality was categorized as very practical according to teacher and student responses. Moreover, the media was proven effective in improving student learning outcomes, as indicated by the increase in post-test scores compared to pre-test scores, with moderate to high improvement levels.